Use of Incisional Negative Pressure Wound Therapy as an Adjunct to Wound Healing in Complex Spine Procedures. (16th November 2020) - Myers, Daniel; Dabecco, Rocco M; Xu, Chen; Yu, Alexander Kwong-Tak
Abstract: INTRODUCTION: Negative pressure wound therapy (NPWT) is a common tool for assistance with wound healing and has proven invaluable in modern wound care. Incisional NPWT in a novel strategy that has demonstrated benefit in the fields of bariatric and orthopedic surgery. There is a paucity of literature addressing the efficacy of incisional NPWT in the setting of spinal surgery. METHODS: This was performed as a retrospective descriptive study. Data was collected over a 12 month period and analzyed for demongraphic, operative, and clinical data. IRB approval was obtained. RESULTS: 105 consecutive cases were identified. 76 patients were treated with iNPWT and 29 patients treated with standard postoperative wound care. In the iNPWT group, there was a significantly higher percentage of non-degenerative pathology including traumatic (11.8% vs 6.9%), infectious (14.4% vs 6.9%) and neoplastic (14.4% vs 13.7%) with degenerative being a higher percentage of cases in the standard therapy group (72% vs 59%). iNPWT patients tended to have larger surgeries average 6.89 instrumented levels, vs 4.07 levels. Risk factors were more common in the iNPWT group including immunocompromised state, diabetes mellitus, cancer, smoking, steroid use, and radiation. Incidence of wound revisions were 10% lower (23.7% vs 34.5%) in the iNPWT group, as were SSI rates (14.4% vs 24.1%). There were no complications related to use of iNPWT. CONCLUSION: Based on these data, iNPWT is a safe and effective adjunct to wound healing via primary intention in complex open spine surgery. Despite a population of patients with a higher incidence of risk factors for SSI and wound complications, the iNPWT group showed a significantly lower incidence of postoperative SSI or need for wound revisions.